Beyond the traditional distinctions of genome editing: evaluating a vulnerability framework - Angelioudaki, Ioanna; Badea, Ana Ruxandra; Bodo, Martina; Fernández-Soto, Daniel; Karyampa, Emmanouela Sevasti; Kokkinakis, Adam; Kolisis, Nikolaos; Kominea, Xenia; Ozáez Armijos, Sandra; Vogel, Simon; Feeney, Oliver (Frontiers in Genome Editing, 2024)
Over forty years ago, the 1982 Splicing Life report outlined the two distinctions that have orientated much of the normative and legal landscape of genetic intervention or genome editing since -that of somatic versus germline (or heritable interventions) and medical versus non-medical (or enhancement) applications. During this time, these distinctions have been used to ethically prioritize some areas of research and potential application, such as somatic treatments, while considering others for prohibition, such as germline enhancements.Nevertheless, somatic interventions may also be done for controversial enhancement purposes while some germline interventions may be done with greater prima facie justification (e.g. the enhancement of athletic ability versus the avoidance of Tay-Sachs disease). Even with new somatic treatments that are generally lauded, exemplified with the case of Casgevy, many issues still arise -such as cost and access, particularly salient on a global level. The concerns over a dystopian future of genetic haves and have nots, as a result of enhancement and/or germline interventions, that perhaps may happen, should not distract us from a greater attention to what is happening in the here and now. In this paper, we will highlight the limits of the two distinctions in terms of moving from questions of "should a technology be used" to "how should a technology be used". We argue that an additional focus on vulnerability and marginalization can be useful to support the attempt to better prioritize which interventions should be permitted or prohibited. We show how this can better dovetail with calls for effective (global) governance and reasonable consensus by focusing on the most urgent issues and developing policy accordingly, while leaving aside more abstract issues for further discussion.